THE IMPLEMENTATION FEATURES OF THE SMART CITY CONCEPT IN KYIV AND VIENNA - Tkach , Solomiia (Collection of scientific papers «ΛΌГOΣ», 2022)
In today’s turbulent conditions, the optimization of urban development processes acquires special value. Among the multitude of urban planning concepts, the concept of smart cities has shown good practical results, which is aimed at ensuring the effective integration of digital, physical and human systems in the artificial environment for the sake of a sustainable, prosperous future for citizens.